Nurse-Patient Relationship Dynamics: A Systematic Review of Factors Influencing Treatment Compliance and Health Outcomes in Chronic Disease Management - Fahad Raheel Al-Suwait, Dalal Dhahawi Aldhafeeri, Hameedah Ayadah Al Shammari, Amairaha Saqar Abdul Razzaq Alanazi, Naiyf Ghnaim Aldhafeeri, Radhyah Ali Kassab Alanazi (Journal of International Crisis and Risk Communication Research, 2024)
Background: The quality of the nurse-patient relationship is a crucial factor in promoting treatment adherence and optimizing health outcomes, particularly in managing chronic diseases that necessitate long-term care. This systematic review aimed to synthesize evidence on the different aspects of the nurse-patient relationship and their impact on patient compliance and clinical results. Methods: A systematic search was conducted in PubMed, CINAHL, PsycINFO, and Embase databases for studies published between 2010-2024 that investigated associations between nurse-patient relationship factors and treatment compliance and/or health outcomes in adult patients with chronic conditions. Both quantitative and qualitative studies were included. Two reviewers independently screened articles, extracted data, and assessed study quality using standardized tools. Results: 32 studies involving 10,580 patients were included. Key factors that positively influenced the nurse-patient relationship and promoted better compliance and health outcomes were: trust and respect between nurse and patient, effective communication and education, empathy and compassion from nurses, continuity of care with the same nurses, adequate time spent with patients, patient involvement in decision-making, and cultural competence of nurses. Factors that negatively impacted the relationship and patient outcomes included lack of trust, poor communication, judgmental attitudes from nurses, frequent changes in nursing staff, time constraints, and cultural/language barriers. Conclusion: This review highlights important nurse and patient-related factors that shape the nurse-patient relationship and ultimately impact treatment adherence and patient well-being in chronic disease management. Nurses and healthcare organizations should prioritize developing trust, empathy, and effective communication skills, allow adequate time with patients, promote continuity of care, engage patients in their care, and provide culturally sensitive services. More high-quality research is needed to evaluate targeted nursing interventions that strengthen these key relationship factors.